Beyond coverage: Can vaccination reduce child mortality despite structural inequality? A global ecological analysis of routine childhood immunization (2010–2023) - Valeria Rios Montoya; Arlet Yelisse Suarez Alarcon; Shamira Perez Castillo; Trilce Zamudio Raez; Antonio Marty Quispe (PLoS ONE, 2026)
Routine childhood immunization is still a critical topic to global public health, since it prevents an estimated 3.5 to 5 million deaths annually. However, its access remains uneven, especially in low-income countries, where structural inequalities limit the reach of immunization programs, and the Covid-19 pandemic disrupted routine services, worsening the existing disparities. This ecological study (2010–2023) examined associations between vaccine coverage and infant mortality using the WHO/UNICEF data for six childhood vaccines: BCG, DTP3, HepB3, Hib3, MCV2, and Pol3. Countries were stratified by income level using the World Bank World Development Indicators. Associations between vaccine coverage and infant mortality were evaluated using multivariable linear regression models adjusted for national income level. In addition, non-linear relationships and rank-based associations were explored using LOESS smoothing and Spearman correlation analyses. Results showed higher coverage and lower mortality in high-income countries; meanwhile, low-income countries faced both reduced coverage and higher mortality rates. A significant decline in coverage occurred in 2020, with only partial recovery by 2023. After adjusting for income, most vaccine coverage indicators lost statistical significance in relation to infant mortality. These findings highlight that income-related structural inequities determine immunization coverage and preventable child mortality, emphasizing the need for policies that simultaneously expand vaccine access, reduce structural barriers, and strengthen health systems.